HUBUNGAN PENDIDIKAN IBU, PRAKTIK PENGASUHAN DAN SANITASI LINGKUNGAN DENGAN KEJADIAN STUNTING PADA BALITA DI DESA LOKUS STUNTING WILAYAH KERJA PUSKESMAS PARON KABUPATEN NGAWI - Qurotul Ainin; Yunus Ariyanto; Citra Anggun Kinanthi (Jurnal Kesehatan Masyarakat, 2023)
Stunting was a condition in which body length or height of toddlers doesn’t meet WHO’s standard, namely under minus 2 of standard deviation. Ngawi Regency had the fourth highest prevalence of stunting in East Java in 2018 with 40.5% cases. Paron Primary Health Center was the area with the most stunting cases and locus in 2022. The purpose of this study was conducted to dertermine the correlation between mother’s education, parenting practice, and environment sanitation with stunting in toddlers. This research is observational study with a case-control design. The samples of this research were 45 cases and 45 control. The sampling technique was proportional stratified random sampling. The analysis of used chi-square test. The results showed that there was correlation between of mother’s education (p = 0,002, OR = 4.429), parenting practice (p = 0,001, OR = 6,833) and environment sanitation (p = 0,042, OR = 4,529) with stunting incidence. The Primary Health Center was need to do consistently provide education on parenting includyng feeding, and personal hygiene of toddlers. Mother should be more give more attention to parenting, especially related to feeding, maintaining the personal hygiene of toddlers, and as well as repairing sanitation facilities.